Physical Activity Patterns during Pregnancy - Borodulin, Katja (2008)
PURPOSE: The aim of the study was to describe the mode, frequency, duration, and intensity of physical activity among pregnant women, to explore whether these women reached the recommended levels of activity, and to explore how these patterns changed during pregnancy. METHODS: This study, as part of the third phase of the Pregnancy, Infection, and Nutrition Study, investigated physical activity among 1482 pregnant women. A recall of the different modes, frequency, duration, and intensity of physical activity during the past week was assessed in two telephone interviews at 17–22 and 27–30 weeks’ gestation. RESULTS: Most women reported some type of physical activity during both time periods. Child and adult care giving, indoor household, and recreational activities constituted the largest proportion of total reported activity. The overall physical activity level decreased during pregnancy, particularly in care giving, outdoor household, and recreational activity. Women who were active during the second and third trimesters reported higher levels of activity in all modes of activity than those who became active or inactive during pregnancy. The majority did not reach the recommended level of physical activity. CONCLUSION: These data suggest that self-reported physical activity decreased from the second to third trimester and only a small proportion reached the recommended level of activity during pregnancy. Further research is needed to explore if physical activity rebounds during the postpartum period.